PERMASALAHAN HUKUM PERKAWINAN BEDA AGAMA DI INDONESIA: STUDI KOMPARATIF - Fitri, Winda; Rusdiana, Shelvi; Anggia Putri, Windi Regina (Jurnal Media Justitia Nusantara, 2024)
Over time, there has been a surge in interfaith marriages between men and women, which has led to a number of social and legal challenges. The Indonesian Conference on Religion and Peace (ICRP) registered 1,655 interfaith weddings from July 19, 2023, and 2005. The year 2023 has drawn significant attention, particularly after the South Jakarta District Court approved interfaith marriages by referring to Article 35, Letter A of Law No. 23 of 2006. Supreme Court Circular Letter No. 2 of 2023, which offers guidance for judges in making decisions pertaining to the registration of marriages between people of various faiths and beliefs, was issued by the Supreme Court in response to this circumstance.